ADHD Medication Use During Pregnancy and Risk for Selected Birth Defects: National Birth Defects Prevention Study, 1998-2011. Issue 3 (February 2020) - Anderson, Kayla N.; Dutton, Annelise C.; Broussard, Cheryl S.; Farr, Sherry L.; Lind, Jennifer N.; Visser, Susanna N.; Ailes, Elizabeth C.; Shapira, Stuart K.; Reefhuis, Jennita; Tinker, Sarah C.
Objective: The objective of this study was to examine the prevalence of, and maternal characteristics associated with, ADHD medication use before and during pregnancy, and associations between early pregnancy ADHD medication use and risk for 12 selected birth defects.Method: We used data from the National Birth Defects Prevention Study (1998-2011), a U.S. population–based case-control study examining risk factors for major structural birth defects.Results: There was an increase in ADHD medication use from 1998-1999 (0.2%) to 2010-2011 (0.5%; p < .001). Early pregnancy ADHD medication use was more commonly reported by mothers of infants/fetuses with gastroschisis (crude odds ratio [cOR]: 2.9, 95% confidence interval [CI] = [1.2, 6.9]), omphalocele (cOR: 4.0, 95% CI = [1.2, 13.6]), and transverse limb deficiency (cOR: 3.3, 95% CI = [1.1, 9.6]).Conclusion: ADHD medication use before and during pregnancy was rare, but the prevalence of use has increased over time. In this analysis, early pregnancy ADHD medication use was associated with three of 12 selected birth defects.